2014
DOI: 10.1007/s10620-014-3291-3
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptional Profiling of Peripheral Blood in Pancreatic Adenocarcinoma Patients Identifies Diagnostic Biomarkers

Abstract: Peripheral blood gene expression profiling is an useful tool for the diagnosis of PDAC. We present a validated four-gene predictor set (ANKRD22, CLEC4D, VNN1, and IRAK3) that may be useful in PDAC diagnosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
27
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(27 citation statements)
references
References 35 publications
0
27
0
Order By: Relevance
“…It codes for a protein with no known function. The ANKRD22 transcripts are increased in the blood of patients with pancreatic cancer 41 or during ovulation. 42 Two transcripts, GBP5 and AIM-2, which were upregulated in all 3 of the tissues we studied, play a role in regulating inflammasomes, which are intracellular proteins that control the activation of IL-1 β.…”
Section: Discussionmentioning
confidence: 99%
“…It codes for a protein with no known function. The ANKRD22 transcripts are increased in the blood of patients with pancreatic cancer 41 or during ovulation. 42 Two transcripts, GBP5 and AIM-2, which were upregulated in all 3 of the tissues we studied, play a role in regulating inflammasomes, which are intracellular proteins that control the activation of IL-1 β.…”
Section: Discussionmentioning
confidence: 99%
“…The co-expression of CXCR6 and CXCL16 , a chemokine ligand and receptor, has been associated with inflammatory response and cell migration [57, 58]. In addition, high levels of HCST [59, 60], C3AR1 [61], GBP4 [62], LY96 [63], ANKRD22 [64], FPR3 [65] and FCGR2A [66], have also been related to immune activation and/or inflammatory response in tumours; however, their role in basal-like breast malignancies are yet to be uncovered. In our study, the increased expression levels of these probes, among others genes in the signature, has brought new insights on the basal-like tumour origin and progression, and Basal I and Basal II differentiation.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that the expression of ANKRD22 in peripheral blood samples can be used for the diagnosis of pancreatic ductal adenocarcinoma 20 . The present study shows, for the first time, that there is an association between the up-regulation of ANKRD22 and tumor progression in NSCLC.…”
Section: Discussionmentioning
confidence: 99%